Three-dimensional finite element analyses of repair process and safety margin assessment. (May 2019) - Chen, Mingya; Yu, Weiwei; Xue, Fei; Fan, Mingyu; Jia, Wenqing; Chen, Zhilin; Ku, Francis; Wang, Weiqiang; Shi, Jinhua
Abstract: An effective repair process is often needed to correct installation slope and geometrical correction of piping, but the repair method, residual stresses (RS), plastic damage and safety margin are needed to be assessed. The results of previous studies indicate that the RS caused by welding process and external correction force are complex, and there may be large local plastic strain damage after the repair process. Fracture toughness of stainless steels (SS) may be reduced significantly by both plastic pre-strain damage and thermal aging effect during the operation. However, there is little public literature to discuss the synergistic action of plastic pre-strain and thermal aging effect. In this paper, three-dimensional finite element (FE) analyses of RS and plastic strain of the repair process are performed, and the synergistic action of plastic pre-strain and thermal aging is analyzed based on the experimental results. In the case study, the repair process is shown to be effective, and the synergistic action is indistinctive as the fracture toughness at saturation state of thermal aging is not significantly affected by the fact of plastic strain. In the study case, the critical failure mode is still the plastic collapse, and the safety margin is increased after the repair process for the typical crack because work hardening is induced by plastic pre-strain. Highlights: 3-D FE analyses of residual stress of the repair welding are performed. The synergistic action of plastic pre-strain damage and thermal aging effect is studied. The critical failure model of piping is analyzed. A generic repair process is given and thus can be applied in similar case.